2008
DOI: 10.1007/s12149-008-0168-6
|View full text |Cite
|
Sign up to set email alerts
|

Could the simplified 14C urea breath test be a new standard in noninvasive diagnosis of Helicobacter pylori infection?

Abstract: Using a combination of invasive diagnostic tests as the gold standard, Heliprobe UBT was found to be highly sensitive and specific for the diagnosis of HP infection in patients with dyspeptic complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
6
0
2
Order By: Relevance
“…They found that Heliprobe had 92% sensitivity, 100% specificity, 100% PPV, 84% NPV, and 94% accuracy [19]. Our results are also in accordance with Ozdemir et al's results for Heliprobe performance (96.6% sensitivity, 100% specificity, 93.7% PPV, 100% NPV, and 97.7% accuracy), although their H. pylori positive gold standard was defined as “positivity of any two of the three following tests (RUT, PCR, and histopathology)” [20]. …”
Section: Discussionsupporting
confidence: 90%
“…They found that Heliprobe had 92% sensitivity, 100% specificity, 100% PPV, 84% NPV, and 94% accuracy [19]. Our results are also in accordance with Ozdemir et al's results for Heliprobe performance (96.6% sensitivity, 100% specificity, 93.7% PPV, 100% NPV, and 97.7% accuracy), although their H. pylori positive gold standard was defined as “positivity of any two of the three following tests (RUT, PCR, and histopathology)” [20]. …”
Section: Discussionsupporting
confidence: 90%
“…The 14 C-UBT (Heliprobe system) is an easy and rapid way with sensitivity of 94% and specificity of 100% for diagnosis of H. pylori infection in patients with dyspeptic complaints 2223…”
Section: Discussionmentioning
confidence: 99%
“…C14 UBT is a reliable and noninvasive technique for the diagnosis of HP infection. The sensitivity of the UBT was 96.6%-100% and its specificity was 76%-100% in different studies (20,23). However in a study from Turkey, the prevalence of HP infection was detected as 68% using the C14 UBT in 1680 patients with variable gastrointestinal complaints (24).…”
Section: Discussionmentioning
confidence: 99%